Anisotropic thermal expansion of Lan(Ti, Fe)nO3n + 2 (n = 5 and 6). (26th February 2013) - Wölfel, Alexander; Dorscht, Philipp; Lichtenberg, Frank; van Smaalen, Sander
<x xml:space="preserve">Abstract</x> Crystal structures are reported for two perovskite‐related compounds with nominal compositions La5(Ti0.8Fe0.2)5O17 and La6(Ti0.67Fe0.33)6O20 at seven different temperatures between 90 and 350 K. For both compounds no evidence of a structural phase transition in the investigated range of temperatures was found. The thermal expansions are found to be anisotropic, with the largest thermal expansion along a direction parallel to the slabs of these layered compounds. The origin of this anisotropy is proposed to be a temperature dependence of tilts of the octahedral (Ti, Fe)O6 groups. It is likely that the same mechanism will determine similar anisotropic thermal behaviour of other compounds AnBnO3n + 2. The crystal structures have revealed partial chemical order of Ti/Fe over the B sites, with iron concentrated towards the centers of the slabs. Local charge compensation is proposed as the driving force for the chemical order, where the highest‐valent cation moves to sites near the oxygen‐rich borders of the slabs. A linear dependence on the site occupation fraction by Fe of the computed valences leads to extrapolated valence values close to the formal valence of Ti4+ for sites fully occupied by Ti, and of Fe3+ for sites fully occupied by Fe. These results demonstrate the power of the bond‐valence method, and they show that refined oxygen positions are the weighted average of oxygen positions in TiO6 and FeO6 octahedral groups.